EKSPLORASI PENGETAHUAN TUMBUHAN OBAT ETNIS SAKAI DI DESA PETANI, DURI-RIAU - Wulandari '; Fitmawati '; Nery Sofiyanti (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Sakai is a local ethnic group in Desa Petani, Duri, Riau Province. The people of this ethnic group still strongly keep their ancestor faith, such as in using medicinal plants. This study aimed to make an inventory of the medicinal plants of Sakai ethnic group in Desa Petani, Duri based on the processing of medicinal plants in disease treatment. This study had been conducted from July 2013 to February 2014. The method used in this study was survey method. The interview of three traditional medicine practitioners were carried out based on a questionnaire list. The results of this research showed that 98 species from 48 families were used as medicinal plants by the Sakai People. The plant part that was mainly used was leaves. The medicinal plants were used by Sakai people in different ways such as being eaten, drunk, lubricated, scrubed and bathed.